Drug development for noise-induced hearing loss. (1st December 2020) - Varela-Nieto, Isabel; Murillo-Cuesta, Silvia; Calvino, Miryam; Cediel, Rafael; Lassaletta, Luis
ABSTRACT: Introduction: Excessive exposure to noise is a common occurrence that contributes to approximately 50% of the non-genetic hearing loss cases. Researchers need to develop standardized preclinical models and identify molecular targets to effectively develop prevention and curative therapies. Areas covered: In this review, the authors discuss the many facets of human noise-induced pathology, and the primary experimental models for studying the basic mechanisms of noise-induced damage, making connections and inferences among basic science studies, preclinical proofs of concept and clinical trials. Expert opinion: Whilst experimental research in animal models has helped to unravel the mechanisms of noise-induced hearing loss, there are often methodological variations and conflicting results between animal and human studies which make it difficult to integrate data and translate basic outcomes to clinical practice. Standardization of exposure paradigms and application of -omic technologies will contribute to improving the effectiveness of transferring newly gained knowledge to clinical practice.